The Dynamic Interplay between the Gut Microbiota and Autoimmune Diseases - Huihui Xu; Meijie Liu; Jinfeng Cao; Xiaoya Li; Danping Fan; Ya Xia; Xiangchen Lu; Jingtao Li; Dahong Ju; Hongyan Zhao (Journal of Immunology Research)
The human gut-resident commensal microbiota is a unique ecosystem associated with various bodily functions, especially immunity. Gut microbiota dysbiosis plays a crucial role in autoimmune disease pathogenesis as well as in bowel-related diseases. However, the role of the gut microbiota, which causes or influences systemic immunity in autoimmune diseases, remains elusive. Aryl hydrocarbon receptor, a ligand-activated transcription factor, is a master moderator of host-microbiota interactions because it shapes the immune system and impacts host metabolism. In addition, treatment optimization while minimizing potential adverse effects in autoimmune diseases remains essential, and modulation of the gut microbiota constitutes a potential clinical therapy. Here, we present evidence linking gut microbiota dysbiosis with autoimmune mechanisms involved in disease development to identify future effective approaches based on the gut microbiota for preventing autoimmune diseases.